Sumba: Dari Pulau Cendana Menjadi Pulau Kapas? - Rambu Luba Kata Respati Nugrohowardhani (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2015)
This paper highlightsthe availability of economic resources which are assumed exists to sustainthe implementation of The National Cotton Acceleration Programme in Sumba. The main question in this paper is: Are there any economic resources to support the national cotton acceleration program to boost rural economic development in Sumba? Instititutional Economics is employed to structure the theoretical point of view. As an alternative perspective in the field of economics, it offers a more comprehensive standpoint to understand implementation of the national program in the island of Sumba than the mainstream economics one.Method being used is document study (a desk study) which data are taken from various kinds of documents. The results of the study shows thatthe two economic resources (land & labor) are available in Sumbabased on the mainstream economics perspectives. However, it can not explain why the existence of those resources failed to boost rural economic development in Sumba. Based on theory of resource process in the light of institutional economics perspectives, availability of resources should be associated with the existence of local institution which attached to the life of local people. Thus, the 'resource' has to beunderstood as definedby the local community in accordance with its function, not only by its abundance. Thus, it can be said that availability of economic resources in Sumba could not be function as factors of production to support the cotton national programm because it ignores the existence of local institutions. Results of this study can be used to carry out more research on the relationship between resources, local institutions, and economic development in rural Sumba.